Tingkat Keberlanjutan Permukiman Pesisir Kelurahan Kota Karang Raya, Kecamatan Teluk Betung Timur, Kota Bandar Lampung - Rafifah, Hana; Putri, Husna Tiara; Bindar, Muhammad Abdul Mubdi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2024)
Spatial planning in coastal settlements must be conducted comprehensively and integratedly. This can be achieved through the application of sustainable coastal settlements in line with SDG goal number 11, which emphasizes sustainable cities and communities. Kota Karang Raya Sub-District has a total area of 0.26 km2 with a population of 1,296 households. The settlement extends from inland towards the coast and is characterized by dense, irregular housing arrangements with inadequate facilities. Being directly adjacent to Lampung Bay's coastline, there is a potential for disasters that can threaten the local community. This research aims to determine the level of sustainability of coastal settlements in Kota Karang Raya Sub-District by identifying the existing conditions and analyzing the level of sustainability. The research adopts a deductive-quantitative approach using descriptive analysis and Multidimensional Scaling (MDS) analysis with assessment categories based on Kavanagh and Pitcher. Based on the MDS analysis, the level of sustainability in the coastal settlements of Kota Karang Raya Sub-District falls into the category of less sustainable with an index value of 47,16. This value represents the coverage of sustainability aspects, with environmental and economic sustainability categorized as less sustainable, while social sustainability is considered relatively sustainable.